Patterns and Severity of PeripheralOpen Access Original Article Vascular Disease in the Pakistani Population - Badshah, Athar; Saif, Anas Bin; Imtiaz, Nauman; Bhatti, Ahsin Manzoor; Khan, Rizwan; Ayubi, Azaz (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the patterns and severity of peripheral vascular diseases (PVD) in a Pakistani population, using CT angiography.Study Design: Prospective longitudinal study.Place and Duration of Study: Department of Vascular Surgery, Combined Military Hospital, Rawalpindi Pakistan, from Aug to Dec 2023.Methodology: A total of 81 adult patients with clinically suspected lower limb PVD were included. Participants underwent a first routine clinical assessment, arterial Doppler, and then lower limb CTA if required to confirm the diagnosis. Patient characteristics, including demographic data and co-morbid conditions, were recorded. The arterial tree was divided into aorto-illiac, femoro-popliteal, and infra-popliteal segments, and the lesions were graded using the TASC-II classification.Results: The study included 62 males (76.5%) and 19 females (23.5%), with a mean age of 62.91±8.99 years. Hypertension (66.7%), diabetes (59.3%), and ischemic heart disease (51.9%) were common comorbidities. Smoking was reported in 49.4% of patients. The most affected segments were the femoro-popliteal arteries (55.6%), followed by the aorto-illiac (45.7%) and the infra-popliteal arteries (34.6%). Multiple segment involvement was noted in 34.6% of cases. Circumferential calcification was observed in 67.9% of patients. Diabetes was significantly less associated with infra-popliteal disease (p=0.035).Conclusion: There is a significant burden of PVD in the Pakistani population, particularly among males and individuals with comorbid conditions such as hypertension, diabetes, and ischemic heart disease. There is a predominance of femoro-popliteal involvement and an advanced nature of atherosclerosis, indicated by prevalent calcification and prevalent type D TASC II disease pattern in different arterial regions.